2016
DOI: 10.14740/jcs309w
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Repair of Vesicouterine Fistula: A Case Report and Mini-Review of the Literature

Abstract: Vesicouterine fistula (VUF) is the rarest form of genitourinary fistulas. Despite the advantages of laparoscopy, there are few case reports showing its feasibility in the management of this rare entity. A 40-year-old woman presented to our department with urinary incontinence associated to cyclic hematuria and amenorrhea. After diagnosis of cervicovesical fistula, the laparoscopic approach was chosen. Catheterization of the fistula tract during cystoscopy at the time of laparoscopy was beneficial to localize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The technique of laparoscopic repair was described in an earlier study by Singh et al [10] Most of the reported literature was either single case report or having fewer case series than the present study or mixed series including vesicovaginal fistula. [11][12][13] Naouar et al [12] described a case of 42-year-old female with transperitoneal laparoscopic VUF repair. The operative time was 165 min and blood loss was 50 mL.…”
Section: Discussionmentioning
confidence: 99%
“…The technique of laparoscopic repair was described in an earlier study by Singh et al [10] Most of the reported literature was either single case report or having fewer case series than the present study or mixed series including vesicovaginal fistula. [11][12][13] Naouar et al [12] described a case of 42-year-old female with transperitoneal laparoscopic VUF repair. The operative time was 165 min and blood loss was 50 mL.…”
Section: Discussionmentioning
confidence: 99%